Increasing the Contrast-To-Noise Ratio of Mri Signals for Regional Assessment of Dynamic Cerebral Autoregulation - Jara-Valencia, J (Springer-Verlag Wien, 2018)
Objective:To devise an appropriate measure of the quality of a magnetic resonance imaging (MRI) signal for the assessment of dynamic cerebral autoregulation, and propose simple strategies to improve its quality. Materials and methods: Magnetic resonance images of 11 healthy subjects were scanned during a transient decrease in arterial blood pressure (BP). Mean signals were extracted from non-overlapping brain regions for each image. An ad-hoc contrast-to-noise ratio (CNR) was used to evaluate the quality of these regional signals. Global mean signals were obtained by averaging the set of regional signals resulting after applying a Hampel filter and discarding a proportion of the lower quality component signals. Results: Significant improvements in CNR values of global mean signals were obtained, whilst maintaining significant correlation with the original ones. A Hampel filter with a small moving window and a low rejection threshold combined with a selection of the 50% component signals seems a recommendable option. Conclusions: This work has demonstrated the possibility of improving the quality of MRI signals acquired during transient drops in BP. This approach needs validation at a voxel level, which could help to consolidate MRI as a technological alternative to the standard techniques for the study of cerebral autoregulation. © Springer International Publishing AG 2018.